1995
DOI: 10.1021/bi00037a033
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Ligand Binding Sites of Fatty Acid and Sterol Carrier Proteins: Effects of Ethanol

Abstract: Direct effects of ethanol on the interaction of cytosolic lipid transfer proteins with ligands are not known. In this study, recombinant liver fatty acid binding protein (L-FABP) and sterol carrier protein-2 (SCP-2) were used in conjunction with a series of fluorescent fatty acid probe molecules to compare the relative dielectric properties of the ligand binding sites and to examine the effects of ethanol in vitro on ligand interaction with these proteins. L-FABP and SCP-2 exhibited broad but distinct ligand s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
115
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(130 citation statements)
references
References 48 publications
14
115
1
Order By: Relevance
“…Use of methanol in the assay could expand the repertoire of ligands that may be tested in this assay by increasing the solubility of lipid compounds under test. While a previous in vitro study showed that ethanol inhibits binding of some fatty acid derivatives to SCP2 [38], in this mass spectrometric assay we did not detect and inhibition of stearoyl CoA binding to SCP2 as a result of addition of methanol up to 25% (v/v). Indeed, although not strictly quantitated, the presence of methanol seemed to enhance stearoyl CoA binding, maybe as a result of improved ligand solubility or more efficient electrospray ionisation (data not shown).…”
Section: Discussioncontrasting
confidence: 92%
“…Use of methanol in the assay could expand the repertoire of ligands that may be tested in this assay by increasing the solubility of lipid compounds under test. While a previous in vitro study showed that ethanol inhibits binding of some fatty acid derivatives to SCP2 [38], in this mass spectrometric assay we did not detect and inhibition of stearoyl CoA binding to SCP2 as a result of addition of methanol up to 25% (v/v). Indeed, although not strictly quantitated, the presence of methanol seemed to enhance stearoyl CoA binding, maybe as a result of improved ligand solubility or more efficient electrospray ionisation (data not shown).…”
Section: Discussioncontrasting
confidence: 92%
“…Furthermore, liver expresses sterol carrier protein-2 (SCP-2), a 13-kDa protein found in peroxisomes and cytosol (25,26), as well as the 58-kDa sterol carrier protein-x (SCP-x) (27). Finally, serum albumin (68 kDa) is also an abundant liver product, although it is not thought to accumulate in the cytosol.…”
Section: Creation Of L-fabp Nullmentioning
confidence: 99%
“…To measure the binding capacity of column fraction III, a fluorescent ligand, saturation-binding assay was performed with cis-parinaric acid. This fatty acid shows low quantum yield and fluorescence intensity in aqueous environment (22) but high quantum yields upon binding to proteins such as L-FABP (22) or SCP-2 (25). Aliquots of fraction III (Fig.…”
Section: Relative Contribution Of L-fabp To the Maximal Fatty Acid Bimentioning
confidence: 99%
See 1 more Smart Citation
“…For over a decade, it was thought that one of the intracellular lipid binding proteins, SCP-2, did not bind fatty acids in the Lipidx-1000 assay and was not involved in fatty acid metabolism (40). However, more recent data using improved fluorescence and 13 C NMR binding assays showed that the SCP-2 binds LCFA (41)(42)(43) and LCFACoA (44) with high affinity, K d values of 200 -400 and 2-4 nM, respectively. Furthermore, SCP-2 also binds branched-chain LCFA (43,45) and may be specifically involved in the peroxisomal oxidation of branched chain LCFA (45,46).…”
mentioning
confidence: 99%